CLIL in action : voices from the classroom - Marsh, David, 1956-; Pérez Cañado, María Luisa; Ráez Padilla, Juan (Cambridge Scholars Publishing, 2015)
This volume explores the current position of CLIL on the three main fronts where it is attracting particular attention in specialized literature, namely, implementation, research, and teacher training. To this end, it presents evidence from national and international research projects, governmentally-financed pedagogical initiatives, grassroots experiences and investigations, and inter-institutional training programs which offer insights into how CLIL is working in action on the afore-mentioned three levels. The opening section of the book ("CLIL in action: Practical considerations") provides a